Menyimak Pemikiran Hukum Islam Satria Effendi - AR, Yusdani (Islamic University of Indonesia, 2007)
The main problem that the writer tries to trace in the following article is Satria Effendiâs Thought of Islamic law. One of the related problem is how to describe Satria Effendiâs theoretical framework and methodology of Islamic law. According to this Islamic law expert to develop Islamic law thought it is urgent need to study the goal of Islamic legislation and public interest especially to response several contemporary problems of Islamic law nowadays. In this context, the using and the integrating or combining the deductive-normative approach model and emphiricalinductive approach model constitutes the necessity because it is a way to produce solutive intellectual exercise in the field of Islamic law. Keywords: maqasid al-syariah, maslahat, ijtihad dan hukum Islam